Controlled and Local Delivery of Antibiotics by 3D Core/Shell Printed Hydrogel Scaffolds to Treat Soft Tissue Infections - Ashwini Rahul Akkineni; Janina Spangenberg; Michael Geissler; Saskia Reichelt; Hubert Buechner; Anja Lode; Michael Gelinsky (MDPI AG, 2021)
Soft tissue infections in open fractures or burns are major cause for high morbidity in trauma patients. Sustained, long-term and localized delivery of antimicrobial agents is needed for early eradication of these infections. Traditional (topical or systemic) antibiotic delivery methods are associated with a variety of problems, including their long-term unavailability and possible low local concentration. Novel approaches for antibiotic delivery via wound coverage/healing scaffolds are constantly being developed. Many of these approaches are associated with burst release and thus seldom maintain long-term inhibitory concentrations. Using 3D core/shell extrusion printing, scaffolds consisting of antibiotic depot (in the core composed of low concentrated biomaterial ink 3% alginate) surrounded by a denser biomaterial ink (shell) were fabricated. Denser biomaterial ink (composed of alginate and methylcellulose or alginate, methylcellulose and Laponite) retained scaffold shape and modulated antibiotic release kinetics. Release of antibiotics was observed over seven days, indicating sustained release characteristics and maintenance of potency. Inclusion of Laponite in shell, significantly reduced burst release of antibiotics. Additionally, the effect of shell thickness on release kinetics was demonstrated. Amalgamation of such a modular delivery system with other biofabrication methods could potentially open new strategies to simultaneously treat soft tissue infections and aid wound regeneration.